1991
DOI: 10.1104/pp.96.3.693
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Galactinol Synthase from Mature Zucchini Squash Leaves

Abstract: Galactinol synthase catalyzes the first committed step in the biosynthesis of raffinose sugars. Previous attempts to purify the enzyme have proven difficult and have resulted in low quantities of unpurified enzyme. Galactinol synthase was purified 752-fold from mature zucchini (Cucurbita pepo L. cv Burpee Hybrid) leaves using sequential liquid chromatography on DE 52, Octyl-Sepharose CL-4B, and Sephacryl S-200. This isolation scheme resulted in an 18.6% recovery of the initial activity. The purified enzyme had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 22 publications
9
34
1
2
Order By: Relevance
“…The pH and temperature profiles obtained for the partially purified enzyme match exactly that obtained with the enzyme sample resulting from the treatment of the seed extract with MnCl 2 (Figure 4A,B). The optimal pH value is comparable to that reported for the GS enzyme from kidney bean cotyledons, which had an optimal pH of 7.0 (Liu et al, 1995), and to that reported for the enzyme purified from zucchini squash leaves, which had a broad pH optima from 7.0 to 8.0, with activity dramatically decreasing below 6.5 and above 8.0 (Smith et al, 1991). The activity of the partially purified GS enzyme was enhanced by MnCl 2 ( Figure 5) and DTT (not shown).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The pH and temperature profiles obtained for the partially purified enzyme match exactly that obtained with the enzyme sample resulting from the treatment of the seed extract with MnCl 2 (Figure 4A,B). The optimal pH value is comparable to that reported for the GS enzyme from kidney bean cotyledons, which had an optimal pH of 7.0 (Liu et al, 1995), and to that reported for the enzyme purified from zucchini squash leaves, which had a broad pH optima from 7.0 to 8.0, with activity dramatically decreasing below 6.5 and above 8.0 (Smith et al, 1991). The activity of the partially purified GS enzyme was enhanced by MnCl 2 ( Figure 5) and DTT (not shown).…”
Section: Resultssupporting
confidence: 59%
“…Although GS has been purified from Cucurbita pepo (Webb, 1982;Smith et al, 1991;Liu et al, 1995) and kidney bean cotyledons (Liu et al, 1995), purification of soybean seed GS has not been reported yet. A partial purification protocol for soybean seed GS and some of the its kinetic properties are therefore reported here.…”
Section: Introductionmentioning
confidence: 99%
“…GS activity was determined as previously described (Smith et al, 1991) with a few modifications. The reaction was carried out in a microfuge tube in a final volume of 100 L, with the following concentrations of substrates: 20 mm myoinositol, 3 mm DTT, 10 mm MnCl 2 , 2 mm UDP-Gal containing 30,000 dpm UDP-[ 14 C]Gal (specific activity Ï­ 59 mCi mmol Ϫ1 ; ICN, Costa Mesa, CA).…”
Section: Enzyme Extraction and Assaymentioning
confidence: 99%
“…Because the only known function of galactinol is the formation of RFOs [Saravitz et al, 1987;Liu et al, 1995], which is putatively the committed enzyme step in the RFO biosynthetic pathway [Pridham and Hassid, 1965;Saravitz et al, 1987;Smith et al, 1991;Peterbauer and Richter, 2001] from UDPgalactose. Thus GolS catalyses the first step in the biosynthesis of galactinol and RFO from UDP-galactose and plays regulatory roles in carbon partitioning between sucrose and RFOs [Saravitz et al, 1987] under the abiotic stress conditions, and that galactinol and rafinose function as osmoprotectants in droughtstress tolerance of plants.…”
Section: Introductionmentioning
confidence: 99%